Effectivity of Erythropoietin Alpha Compared to Erythropoietin Beta in Patients with Chronic Kidney Disease-Anemia on Hemodialysis - Prasetya, Anak Agung Ngurah Putra Riana; Suprapti, Budi; Shanti, Bayu Dharma (Folia Medica Indonesiana, 2019)
Anemia in patient with chronic kidney disease could cause a lot of complication. The first line therapy of this condition is by treating with erythropoiesis-stimulating agents (ESA) or called erythropoietin. The erythropoietin alpha and beta were two types of the human recombinant erythropoietin that are usually used in Indonesia. The aim of this study was to determine the effectivity of erythropoietin alpha compared to erythropoietin beta especially in haemoglobin and haematocrit level. This prospective observational study was conducted in March – September 2016. The inclusion criteria were CKD stage 5 patients with a minimum of 3 months of regular hemodialysis, Hb <10 g/dL with enough iron status ST > 20% and FS > 200ng/mL. The methology of this study had been approved by the Health Research Ethics Committee of the Bhayangkara H.S. Samsoeri Mertojoso Hospital, Surabaya. Patients received 2000 IU subcutaneous erythropoietin twice a week on both groups. Blood sample was withdrawn in pre-treatment and after 4 weeks of post erythropoietin therapy treatment for measurement of haemoglobin and haematocrit. Target for this erythropoietin therapy are increase of Hb 0.5 – 1.5 g/dL (not to exceed 12 g/dL) and increase of Hct level 2 – 4 % in 4 weeks. Based on the inclusion criteria, there were 20 patients in this study (10 patient each of both erythropoietin alpha either beta group) that consist of 7 women and 13 men. After the treatment, the mean of increased haemoglobin level for erythropoietin alpha group was 1.28 ± 0.80 g/dL (p=0.001) and erythropoietin beta was 0.37 ± 0.95 g/dL (p=0.254). The mean of increased haematocrit level for erytropoietin alpha group was 3.56 ± 3.46 % (p=0.010) and erythropoietin beta was 1.34 ± 2.71 % (p=0.152). In comparison of haemoglobin and haematocrit achievement in both groups showed that erythropoietin alpha gave better achievement in haemoglobin parameter (p=0.033), but there were no differences in both groups on haematocrit parameters (p=0.127).